Size-controllable synthesis of NiCoSe2 microspheres as a counter electrode for dye-sensitized solar cells. Issue 46 (19th July 2018) - Chen, Xiaobo; Ding, Jingguo; Li, Yan; Wu, Yinxia; Zhuang, Guoce; Zhang, Cuicui; Zhang, Zhihai; Zhu, Chengyun; Yang, Peizhi
Abstract : The PCE value of the NiCoSe2 -150-based DSSC is 8.76%, which is higher than that of DSSCs based on Pt (8.22%). Abstract : NiCoSe2 microspheres have been successfully synthesized by a facile one-step hydrothermal method at different hydrothermal temperatures. The prepared samples are divided according to their reaction temperatures (90, 120, 150 and 180 °C) and named NiCoSe2 -90, NiCoSe2 -120, NiCoSe2 -150 and NiCoSe2 -180, respectively. The diameters of the NiCoSe2 microspheres strongly depend on the different hydrothermal temperatures. When the temperature is increased to 150 °C, the size of the resultant NiCoSe2 microspheres changes from 200 to 800 nm, and the interior of NiCoSe2 -150 possesses a flocculent structure. However, NiCoSe2 -180 displays a cauliflower-like aggregated structure. The prepared NiCoSe2 alloys are used as high-performance Pt-free counter electrodes (CEs) for dye-sensitized solar cells (DSSCs). Cyclic voltammogram measurement indicates that NiCoSe2 -150 CE has larger current density than Pt CE. Electrochemical impedance spectroscopy shows that NiCoSe2 -150 CE has a low charge-transfer resistance of 1.8 Ω cm 2 . Due to their unique morphologies and well-defined interior and exterior structures, DSSCs based on NiCoSe2 -120 and NiCoSe2 -150 CEs achieve high power conversion efficiencies of 8.48% and 8.76%, respectively, which are higher than that of the solar cell based on Pt CE (8.31%).